pharmaceutical prédiction and biological activities of Solenostemma argel in vitro and in silico study - Belloul Radhia; Ben bordi sabrine (جامعة الوادي university of eloued, 2026)
This study aimed to evaluate the pharmaceutical prediction and biological activities of Solenostemma argel using both in vitro and in silico approaches. The work focused on the extraction, phytochemical screening, characterization, and biological evaluation of the plant extract, with particular attention to its anti-inflammatory, anti-hemolytic, and antidiabetic potential. Phytochemical screening revealed the presence of several secondary metabolites, mainly alkaloids and cardiac glycosides, with weaker detection of flavonoids and tannins. The extract was characterized using UV-Visible spectroscopy and HPLC, which confirmed the presence of alkaloid-related compounds. The anti-inflammatory activity was evaluated through the inhibition of BSA denaturation. The results showed a concentration-dependent inhibitory effect, with inhibition increasing from 30.736% to 60.833%. The IC50 value of Solenostemma argel extract was 0.432 µM, indicating a measurable anti-inflammatory activity, although lower than that of the reference drugs diclofenac and prednisolone. The anti-hemolytic test showed that the extract improved red-blood-cell protection as concentration increased, but its effect remained lower than that of aspirin. In addition, the extract showed promising antidiabetic activity through α-amylase inhibition, with an IC50 value of 0.1867 µM compared with 0.2091 µM for acarbose. The in silico study supported the experimental results. SwissADME prediction indicated acceptable physicochemical and pharmacokinetic properties, while ProTox results suggested no predicted hepatotoxicity, carcinogenicity, mutagenicity, or cytotoxicity. Molecular docking also showed a negative binding energy with cyclooxygenase-2, suggesting a possible interaction with this inflammatory target. Overall, Solenostemma argel demonstrated promising biological potential, particularly as a natural source of anti-inflammatory and antidiabetic bioactive compounds. However, further studies are required to isolate the active molecules, confirm their mechanisms of action, and evaluate their safety and efficacy in vivo.
CD
Keywords: Solenostemma argel; alkaloids; anti-inflammatory activity; anti-hemolytic activity; antidiabetic activity.